2021
DOI: 10.3311/ppci.18901
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength Prediction of FRP-reinforced Concrete Beams Using an Extreme Gradient Boosting Framework

Abstract: Despite the importance and accuracy of empirical models, most of the existing models are only accurate on the collected experimental data. Adding new data, or even considering noise or variance in the data leads to loss of model accuracy. The objective of this paper is to alleviate overfitting and develop a more accurate and reliable alternative method using a decision-tree-based ensemble Machine Learning algorithm that uses a gradient boosting framework for the prediction of the ultimate shear strength of FRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, the activation function (f) plays a crucial role in transforming the weighted sum of inputs (z) in each neuron: a = f(z). (Kaveh et al, 2022). Each tree learns from the errors of the previous one, resulting in improved prediction accuracy.…”
Section: Correlation Analysismentioning
confidence: 99%
“…However, the activation function (f) plays a crucial role in transforming the weighted sum of inputs (z) in each neuron: a = f(z). (Kaveh et al, 2022). Each tree learns from the errors of the previous one, resulting in improved prediction accuracy.…”
Section: Correlation Analysismentioning
confidence: 99%
“…The result indicates that the proposed model was able to make superior predictions compared to the remaining methods. Ali et al [58] used the extreme gradient boosting method (XGBoost) for developing a shear prediction model for FRP-reinforced concrete beams without transverse reinforcements. To utilise the complete dataset K-fold cross-validation technique was implemented in this investigation.…”
Section: Sanad and Sakamentioning
confidence: 99%
“…It was also observed that the UHPC and FRC models available in the literature underestimated shear capacity. Kaveh et al [84] proposed novel ML models for predicting the shear strength of beams without stirrups and reinforced with FRP bars using three different algorithms. They employed LASSO regression, RF, and XGBoost to develop new prediction models.…”
Section: Mohammed and Ismailmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the traditional AI methods such as ANN have a few shortcomings such as local minima trap issue [ 32 , 33 , 34 , 35 ]. In order to circumvent these issues, researchers utilised various other AI methods such as support vector machine (SVM), random forest (RF), gradient boosting machine (GBM), ensemble trees (ET), and extreme gradient boosting (EGB), etc., in predicting the strength of FRP-reinforced concrete [ 36 , 37 , 38 , 39 ]. Chen et al [ 40 ] developed an ensemble learning-based gradient-boosted regression tree (GBRT) model to estimate FRP-concrete interfacial bond strength using 520 samples.…”
Section: Introductionmentioning
confidence: 99%